Therapeutic equivalence of two amlodipine preparations (original and generic) in patients with arterial hypertension. Results of a double-blind, randomized cross-over study - S. Yu. Martsevich; N. P. Kutishenko; A. D. Deev; E. V. Alimova; Yu. E. Semenova (Российский кардиологический журнал)
The aim of the study was to assess in a double-blind, cross-over randomized trial the therapeutic equivalence of two amplodipine preparations (Cardilopin® and Norvasc®) in patients with arterial hypertension (AH). Thirty individuals with mild to moderate AH (mean age 61,2+1,7) were examined. All participants were treated with Cardilopin® and Norvasc® in six-week courses; the course consequence was randomized. The initial daily dose of amlodipine was 5 mg, in non-responders it was increased to 10 mg 2 weeks later. Treatment efficacy was assessed by rest blood pressure (BP) dynamics. Patients started the treatment with Norvasc® or Cardilopin® did not differ by main clinical characteristics. During Cardilopin treatment, systolic BP (SBP) lowered from 155,7+2,1 mm Hg to 138,8 ±1,5 mm Hg (p<0,001), diastolic BP (DBP) decreased from 95,4±l,2 mm Hg to 87,l±l,5mm Hg(p<0,001). Heart rate (HR) slightly increased -from 74,1±1,7 beats per minute (bpm) to 77,8±2,2 (non-significant). During Norvasc® treatment, SBP lowered from 156,3+2,1 mm Hg to 135,3 ±2,0 mm Hg (p<0,001), and DBP-from 95,2+1,5 mm Hgto 84,6+1,0 mm Hg (p<0,001). HR increased from 74,0+1,6 79,1+1,7 bpm (p<0,05). Authors conclude that Cardilopin® is equal to the «gold standard» amlodipine preparation, Norvasc®, by main clinical characteristics, and both medications are therapeutically equivalent to each other.